Dual catalytic enantioselective desymmetrization of allene-tethered cyclohexanones - Zhang, L; Yamazaki, K; Leitch, JA; Manzano, R; Atkinson, AM; Hamlin, TA; Dixon, DJ (Royal Society of Chemistry, 2020)
The construction of enantioenriched azabicyclo[3.3.1]nonan-6-one heterocycles via an enantioselective desymmetrization of allene-linked cyclohexanones, enabled through a dual catalytic system, that provides synchronous activation of the cyclohexanone with a chiral prolinamide and the allene with a copper(I) co-catalyst to deliver the stereodefined bicyclic core, is described. Successful application to oxygen analogues was also achieved, thereby providing a new enantioselective synthetic entry to architecturally complex bicyclic ethereal frameworks. The mechanistic pathway and the origin of enantio- and diastereoselectivities has been uncovered using density functional theory (DFT) calculations.